Evaluation the impact of Earning quality on banking Hedging ، an applied study on the sample of banking which are listed on the IRAQI Stock Exchange for the period(2014-2017) - Ahmed youcef, Raoue; Riyad abdellah, Raghad (Finance and Business Economies Review, 2020)
This research deals with subject of the quality of bank profits, as one of the important topics related to the banking safety .Through apply the theoretical and practical analysis of the each of profit quality and banking safety . As well as , measuring the impact of profit quality on the banking safety for the sample of banking which are listed on the IRAQI STOCK Exchange for the period (2014-2017 ) . for achieving the research objectives , require formulated the hypothesis that refer to there is a significant effect of the quality of profits on the banking safety . Where this hypothesis have been examined statistically by using SPSS program .The research reach to a set of conclusions , the most important one of which the existence a relationship between the two variables of study . Also , there is a significant impact of the quality of profits on banking safety .Finally , the research presented a set of recommendations , like the bank managers need to pay attention for achieving the high-quality profits for their importance and significant impact on banking safety .